Transcriptional insights into Cu related tolerance strategies in maize linked to a novel tea-biochar. (15th January 2022) - Pehlivan, Necla; Wang, Jim J.
Abstract: One-third of maize cultivation in Turkey has been performed in nutrient-rich soils of the coastal agricultural lands of the Black Sea Region, which is among the country's granaries. However, the yield of this chief crop is affected by Cu toxicity due to a decades-long abandoned opencast Cu-mine. As part of the modern agenda, against this problem, we valorized one of the region's signature plant waste by synthesizing a tea-derived biochar (BC) and evaluated for remediation effect on maize Cu tolerance. Among other rates (0%, 0.4%, 0.8%, 1.6%), maximum Cu absorption (168.27 mg kg −1 ) was found in the 5%BC in in-vitro spiking experiments where natural Cu contamination levels were mimicked. Obvious increasing trends in both root and shoot tissues of maize plantlets growing in Cu-spiked soil (260.26 ± 5.19 mg Cu kg −1 ) were recorded with proportionally increasing BC application rates. The black tea waste-BC (5%) amendment remarkably reduced the Cu uptake from Cu spiked-soil and showed no phenotypic retardation in maize. Accordingly, it boosted the metabolic and transcriptomic profile owing to up-regulation in the aquaporin and defense genes ( PIP1;5 and POD1 ) by 1.31 and 1.6 fold. The tea-BC application also improved the soil-plant water relations by minimizing cytosolic volume changes between 85 and 90%, increasing chlorophyll intactness (65%) and membrane stability up to 41%. The tea-BC could be a strong agent with potential agronomic benefits in the remediation of the cationic Cu toxicity that occurred in the mining-contaminated agricultural soils. Graphical abstract: Image 1 Highlights: Tea-BC might be a promising material in decreasing post-mining agricultural pollution. Pyrolyzed nutrient-rich black tea waste enhanced toxic Cu(II) adsorption. Tea-BC masked the negative effects of Cu(II) boosted the biomass and decreased phytotoxicity. Massive changes in POD1 and PIP1;5 did not occur upon tea-BC yet both regulated <2 fold. Transcript abundances significantly correlated with the morphophysiological traits. Abstract : The tea-BC boost the metabolic and transcriptomic profile that favors up-regulation of aquaporin and defense genes ( PIP1;5 and POD1 ) that lead to enhanced ROS detoxification and soil-plant water relations.